2005
DOI: 10.1093/ajcn/81.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cobalamin deficiency compared with that of cobalamin absorption on serum holo-transcobalamin II

Abstract: Metabolic cobalamin status is a major determinant of serum holo-TC II. Absorption status may have mild influence as well, although other explanations remain possible. Serum holo-TC II cannot be used clinically to diagnose cobalamin malabsorption because of overlap with normal values. The influences on holo-TC II are complex and require careful analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…However, according to Chen et al, HoloTC concentrations most probably reflect vitamin B 12 status independently of its recent absorption (22). Questions are still raised concerning the specificity of the HoloTC assay.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Chen et al, HoloTC concentrations most probably reflect vitamin B 12 status independently of its recent absorption (22). Questions are still raised concerning the specificity of the HoloTC assay.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring holo-TC-II is believed to reflect the bioavailable vitamin B12 as the protein is responsible for the immediate transfer of the newly absorbed vitamin from the ileal enterocytes to the target cells. Chen et al found that the metabolic status of vitamin B12 was a major determinant of holo-TC-II serum levels (64). Furthermore, they concluded that the absorption status of vitamin B12 also influenced serum holo-TC-II levels.…”
Section: Holo-tc-ii Testmentioning
confidence: 99%
“…The laboratory evaluation of B 12 status follows different strategies whose advantages and disadvantages are intensely debated [8,9,[11][12][13][14][15][16][17]. Measurement of the total B 12 in blood plasma (Cbl-saturated HC [holoHC] + holoTC) has been used for decades because of the simplicity of the method.…”
Section: Introductionmentioning
confidence: 99%